2021
DOI: 10.3390/cancers13163950
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of Growth Hormone-Releasing Hormone Inhibit the Growth of Pituitary Adenoma Cells by Hampering Oncogenic Pathways and Promoting Apoptotic Signaling

Abstract: Pituitary adenomas (PAs) are intracranial tumors, often associated with excessive hormonal secretion and severe comorbidities. Some patients are resistant to medical therapies; therefore, novel treatment options are needed. Antagonists of growth hormone-releasing hormone (GHRH) exert potent anticancer effects, and early GHRH antagonists were found to inhibit GHRH-induced secretion of pituitary GH in vitro and in vivo. However, the antitumor role of GHRH antagonists in PAs is largely unknown. Here, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(134 reference statements)
1
7
0
Order By: Relevance
“…We have previously demonstrated the ability of MIA-602 and MIA-690 to inhibit in vitro PM cell proliferation and viability and cMyc expression [ 29 ], a result confirmed here in vivo, where mice treated with MIA-690, either alone or with cisplatin/pemetrexed, showed reduced cMyc expression in PM tumors. Accordingly, the anticancer effects of MIA-690 and the downregulation of cMyc were recently shown by our group in vitro, in pituitary adenoma cell lines [ 44 ], and in a collaborative study by Recinella et al in colorectal cancer in mice, where an increase in p53 protein levels and inhibtion of COX-2, iNOS, and NF-kB gene levels were also observed [ 23 ]. Accordingly, our present results show that MIA-690 potentiates the effect of cisplatin/pemetrexed in PM xenografts also on inhibition of NF-kB, assessed as phosphorylation of p65 subunit, and STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We have previously demonstrated the ability of MIA-602 and MIA-690 to inhibit in vitro PM cell proliferation and viability and cMyc expression [ 29 ], a result confirmed here in vivo, where mice treated with MIA-690, either alone or with cisplatin/pemetrexed, showed reduced cMyc expression in PM tumors. Accordingly, the anticancer effects of MIA-690 and the downregulation of cMyc were recently shown by our group in vitro, in pituitary adenoma cell lines [ 44 ], and in a collaborative study by Recinella et al in colorectal cancer in mice, where an increase in p53 protein levels and inhibtion of COX-2, iNOS, and NF-kB gene levels were also observed [ 23 ]. Accordingly, our present results show that MIA-690 potentiates the effect of cisplatin/pemetrexed in PM xenografts also on inhibition of NF-kB, assessed as phosphorylation of p65 subunit, and STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, TP53, encoding p53, is the most commonly mutated gene in human cancers, and the deletion of Pten and TP53 in mouse mesothelium results in the development of non-epithelioid mesothelioma [ 43 ]. We have previously demonstrated that MIA-602 and MIA-690, in addition to displaying antitumor activities, increase the expression of p53 in human PM cell lines [ 29 ], as well as in GH/prolactin-secreting pituitary adenoma cell lines [ 44 ] and colorectal cancer cells [ 23 ]. Furthermore, earlier GHRH antagonists counteracted the mitogenic effects of GHRH in lung cancer cell lines by increasing p53 and inhibiting MAPK activation, as well as the expression of inflammatory iNOS, COX-2 and NF-kB [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the tumor would not be a candidate to somatostatin receptor inhibitors, as the somatostatin receptor expression was low, as well. However, the expression analysis showed high overexpression of PRLR and GHRHR , both of these receptors representing known targets for chemotherapy in cancer [ 53 , 54 ]. Prolactin binds PRLR that in turn recruits and activates the JAK-STAT5 pathway, inducing a proliferating response through cyclin D1 transcription [ 55 ].…”
Section: Discussionmentioning
confidence: 99%